Figurative Language in Song lyrics My Way by Frank sinatra - Anna Catharina Samosir; Martina Girsang Girsang; Bernardus Batara Tuahta Praditya Ginting; Asima Rohana Parulian Tamba; Jessica Anastasia Kianlin (Institut Agama Islam Negeri Palopo, 2023)
Interest in the meaning ofÂ song lyrics â€œMy Wayâ€ by Frank Sinatra has made the writers do this research. This research aims to know how many types and what is the meaning of figurative language used by the song writer in this song lyrics. In this song lyrics the writers found four types of figurative language, they are: metaphor, repetition, hyperbole, and paradox. The writers took the song lyrics from genius.com/Frank-Sinatra-my-way-lyrics. The dominant types are metaphor and repetition. They are used to show and to say his/her feeling and the experienced too. The feelings and the experiences are the happy and the sad one. Actually, how to face this life it depends on the person. Finally, he/she the one who face what the life brings to his way.